Synthesis of photocleavable protected terminal alkynes for self-assembled monolayers and single molecule electronics - Peltonen, Petra (2021)
The theoretical part of the thesis introduces self-assembled monolayers, their applications in a view of organic electronics and usage of photocleavable protection groups. Alkanethiol SAMs on gold surface and their surface modifications in a different approach are focused. Theoretical work also contains some information about traditional protection groups and synthesis which are related to the experimental part. The aim of experimental part was to synthesize a photocleavable protected arylpropiolic acid with an alkanethiol anchoring group and apply it on a gold surface. Prepared monolayer could be used for surface modification and release the terminal alkyne by light activation for further reactions. If experiment could succeed, there is a potential to create a single molecule electronics. As a result, the formation of self-assembled monolayer could not prove via used characterization methods.